(untitled) (Conference Zone, 2022)
The increasing complexity of educational tasks gives special importance to the study of the role of image and clothing as one of the professionally important qualities of a modern teacher, educator. The modern conditions in which we live and work are fundamentally different from what they were before. And in the new conditions, we should behave and live differently, in proportion to other models of behavior of kindergarten teachers.